Heavy Chronic Ethanol Exposure From Adolescence to Adulthood Induces Cerebellar Neuronal Loss and Motor Function Damage in Female Rats - da Silva, Fernando B. R.; Cunha, Polyane A.; Ribera, Paula C.; Barros, Mayara A.; Cartágenes, Sabrina C.; Fernandes, Luanna M. P.; Teixeira, Francisco B.; Fontes-Júnior, Enéas A.; Prediger, Rui D.; Lima, Rafael R.; Maia, Cristiane S. F. (Frontiers in Behavioral Neuroscience, 2018)
Over the last years, heavy ethanol consumption by teenagers/younger adults has increased considerably among females. However, few studies have addressed the long-term impact on brain structures’ morphology and function of chronic exposure to high ethanol doses from adolescence to adulthood in females. In line with this idea, in the current study we investigated whether heavy chronic ethanol exposure during adolescence to adulthood may induce motor impairments and morphological and cellular alterations in the cerebellum of female rats. Adolescent female Wistar rats (35 days old) were treated with distilled water or ethanol (6.5 g/kg/day, 22.5% w/v) during 55 days by gavage. At 90 days of age, motor function of animals was assessed using open field, pole, beam walking and rotarod tests. Following completion of behavioral tests, morphological and immunohistochemical analyses of the cerebellum were performed. Chronic ethanol exposure impaired significantly motor performance of female rats, inducing spontaneous locomotor activity deficits, bradykinesia, incoordination and motor learning disruption. Moreover, histological analysis revealed that ethanol exposure induced atrophy and neuronal loss in the cerebellum. These findings indicate that heavy ethanol exposure during adolescence is associated with long-lasting cerebellar degeneration and motor impairments in female rats.